2016
DOI: 10.1016/j.joms.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Analysis of Mandibular Angle Fractures: Epidemiology, Patterns, Treatments, and Outcomes

Abstract: Although the Champy technique and reconstruction plates were associated with better postoperative outcomes, such as patient comfort and fracture healing, these should not be used interchangeably. IMF and extraction versus retention of teeth in the line of fracture did not influence any of the outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 34 publications
4
24
0
6
Order By: Relevance
“…Another study on mandibular angle fracture reported similar epidemiologic data. Patel et al3 showed that the overwhelming majority of patients were men, comprising 85 of 103 patients (82.5%), whereas women accounted for 18 of 103 patients (17.5%) with mandibular angle fracture. Most fractures occurred at the left mandibular angle (34.9%), followed by the right side (34.9%) and both sides (5.8%).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another study on mandibular angle fracture reported similar epidemiologic data. Patel et al3 showed that the overwhelming majority of patients were men, comprising 85 of 103 patients (82.5%), whereas women accounted for 18 of 103 patients (17.5%) with mandibular angle fracture. Most fractures occurred at the left mandibular angle (34.9%), followed by the right side (34.9%) and both sides (5.8%).…”
Section: Discussionmentioning
confidence: 99%
“…The issue of postoperative infection has long been debated and represents a common complication of mandible angle fracture3. A 1994 study by Ellis and Walker12 found that the extraction of third molars in fracture lines seemed to increase postoperative infection3413.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations